My love mix-up! Vol. 4 - Hinekure, Wataru (Shojo beat manga., 2022)
"Aoki has a crush on Hashimoto, the girl in the seat next to him in class. But he despairs when he borrows her eraser and sees she's written the name of another boy--Ida--on it. To make matters more confusing, Ida sees Aoki holding that very eraser and thinks Aoki has a crush on him! Aoki confesses his feelings to Ida and prepares for rejection, but in an unexpected turn of events, Ida asks him if they should try dating. Aoki wants to keep their new relationship under wraps, but Ida has already told all their friends!"--Amazon.